2018
DOI: 10.1002/cam4.1458
|View full text |Cite
|
Sign up to set email alerts
|

Cervical lymph node carcinoma metastasis from unknown primary site: a retrospective analysis of 154 patients

Abstract: Despite advances in diagnosis and treatment, the existence of cervical lymph node carcinoma of unknown primary site (CCUP) has always been an urgent problem worldwide. There is still no consensus on the optimal management for CCUP. In this retrospective review, we analyze the clinical characteristics of CCUP patients treated at our institution and examine how these characteristics and treatments were associated with survival. Clinicopathologic features, treatments, and survival outcomes of 154 CCUP patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 21 publications
(24 reference statements)
2
32
1
1
Order By: Relevance
“…Bilateral metastases were found in 8.7% and unilateral in 92.3%, more often on the left side 25. According to Yan Wang et al, N1 was found in 50%, N2 in 40% and N3 in 9.2% of the patients 1…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Bilateral metastases were found in 8.7% and unilateral in 92.3%, more often on the left side 25. According to Yan Wang et al, N1 was found in 50%, N2 in 40% and N3 in 9.2% of the patients 1…”
Section: Discussionmentioning
confidence: 96%
“…Carcinoma of the unknown primary site (CUP) is a neoplasm in which there are metastases to the lymph nodes and distant metastases but the detection of a primary focus is not feasible 1. CUP involves 2–5% of head and neck neoplasms 1. It is more often found in men with the mean survival time of 36 months starting from the appearance of the lesion in the neck 2.…”
Section: Introductionmentioning
confidence: 99%
“…However, the treatment strategies have been controversial, until now 6 , 8 , 9 . Although radiation therapy with or without neck dissection, including irradiation of all potential mucosal disease sites, has been effective, it causes substantial morbidity and side effects 6 , 14 . Therefore, efforts should be made to find the primary tumor, as this allows a more focused therapy, with less morbidity, and possibly a better outcome 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The added sensitivity of RFA for detecting occult palatine tonsil SCC was 34.6% over conventional MRI and it was comparable to 18 F-FDG PET/CT. Despite recent advances in diagnostic tools for use in head and neck cancers, it is common to encounter patients who present with cervical lymph node metastasis without an apparent primary site following thorough clinical and radiological examinations 6,14 . In previous studies, SCC was the most common histologic type, accounting for 78% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,9,12,14,29e31 Looking at unknown primary cases in particular the reported range is 36e59%. 30,31 The reasons for this are unclear although it is possible that patients in the region present at a later clinical stage. Although increased prevalence could increase the positive predictive value, this prevalence was not known while the study was being conducted and it is hoped that this did not adversely impact the results.…”
Section: Limitationsmentioning
confidence: 99%